Effect Of Training Methods And Hand Eye Coordination On Dribbling Skills In Basketball Games In Athletes Of Perbasi Bone Regency - Hudain, Muh Adnan; Suwardi, Suwardi; Nawir, Nukhrawi; Arimbi, Arimbi; Wirawan R, Andi (Hanoman Journal: Physical Education and Sport, 2023)
This research includes 2x2 factorial experimental research. The population of this study were all Bone Regency PERBASI athletes with a total research sample of 40 athletes. Then the sample distribution technique uses ordinal maching. The data analysis technique used is the 2X2 factorial analysis technique and the tukey test using the SPSS Version 26.00 system at a significant level of 95% or a0.05.Based on the results of data analysis it can be concluded that: (1) There is a difference in the effect of the drill training method and the inclusion training method on dribbling skills in Bone Regency PERBASI Athletes, obtained Fhitung = 9.512> Ftabel = 4.113, or significant = 0.004 <0.05 and the inclusion training method is better than the drill training method. (2) There is an interaction of training methods and hand eye coordination on dribbling skills in Bone Regency PERBASI athletes, obtained Fhitung = 59.736 > Ftabel = 35.343, or significant = 0.000 < 0.05, (3) There are differences in dribbling skills between high hand eye coordination groups using the drill training method and the inclusion training method, with a significant value of 0.000 <0.05, and high hand eye coordination trained using the nclusi training method is better than those trained using the drill training method and (4) There are differences in dribbling skills between low hand eye coordination groups using the drill training method and the inclusion training method, with a significant 0.012.